Baitul Maal Sebagai Lembaga Keuangan Islam Dalam Memperlancar Aktivitas Perekonomian - Agus Marimin (Jurnal Akuntansi dan Pajak, 2014)
This study aims to determine the scope, purpose, and function of the baitul mall as an Islamic financial institution in facilitating the existing economic activity in the community. The method of research in this study using literature study by studying various literature related to research studied. The result of the research indicates that the scope of baitul maal that Baitul Maal is an institution or agency which is responsible to handle the state's wealth especially finance, whether related to the matter of income and management as well as related to the issue of expenditure and others or receiving, storing and distributing money state in accordance with the rules of Shari'a. The purpose and function of baitul maal is the realization of zakat collection service, infaq, shodakoh and wakaf which optimize value for muzaki, munfiq, tatasaddiq, and muwafit. The second is the realization of ziswaf empowerment services that optimize the network based levy-based mustahiq empowerment efforts. And also the realization of the organization as a good organization that optimizes value for stakeholders.